Interrogating the Construct of PRETCO-Oral: Longitudinal Evidence From Raters and Test-Takers - Yang, Zhiqiang; Zeng, Yongqiang; Li, Zhifang; Lin, Zhiqing (Frontiers in Psychology, 2022)
Abstract: Construct in language testing can be defined in three ways, namely ability-focused, interaction-focused and task-focused (Bachman 2007). The Practical English Test for College Oral (PRETCO-Oral) comprises four tasks, i.e. Reading aloud, Question and Answer, Interpretation and Presentation, the construct of which appears to touch on the aforementioned three ways of construct definition. This study explores the construct validity of PRETCO-Oral through analysis of data retrieved from various sources, including longitudinal ratings of test-takers’ performances across four occasions, perceptions upon the construct of PRETCO-Oral from both raters and test-takers. The results indicate that raters’ ratings keep stable and the PRETCO-Oral assessment is equipped with longitudinal reliability; tasks of Interpretation and Presentation represent a large amount of variance of the construct, while those of Reading Aloud and Question and Answer seem to be construct-underrepresented, as evidenced via analyzing the data collected from perceptions of raters and test-takers upon the test construct. Finally, factors that threaten the construct representation are also discussed.